Analysis Of the Presentation of Financial Statements and Realization of the APBDes Tanjung Negara Kec. Kedurang Kab. South Bengkulu - Nopita Sari; Yun Fitriano; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the suitability of the presentation of financial statements and the realization of the Regional Budget of Tanjung Negara Kec. Kedurang Kab. Bengkulu Selatan Year 2019 based on Permendagri No. 20/2018 This type of research is comparative description, data collection methods are observation, interviews, documentation, while the data analysis techniques used in comparative description analysis research are data collection, comparing, analyzing, and drawing conclusions. the results of this study found that the presentation of financial reports and the realization of the APBDes Tanjung Negara kec. Kedurang Kab. Bengkulu Selatan has cooperated with Minister of Home Affairs Regulation No. 20/2018 but still found difficulties, namely the absence of financial assistance from South Bengkulu district and provincial financial assistance, which are not listed in the APBDes realization report. Furthermore, in the financial report of Desa Tanjung Negara Kec. Kedurang Kab. South Bengkulu does not have district financial assistance and provincial financial assistance, Village Assets in the Notes to Complete Financial Statements as in the Regulation of the Minister of Home Affairs Regulation No. 20 of 2018.